2012
DOI: 10.3176/earth.2012.4.07
|View full text |Cite
|
Sign up to set email alerts
|

More about the Ordovician–Silurian transition beds at Mirny Creek, Omulev Mountains, NE Russia: carbon isotopes and conodonts

Abstract: Profound environmental and biodiversity changes take place in the Ordovician–Silurian boundary interval. The Mirny Creek and Neznakomka River bank sections discussed in this paper expose the upper Katian–lower Rhuddanian part of the boundary beds. The succession consists of carbonate rocks, partly with bioherms, alternating with argillaceous and siltstone packages that are well dated by graptolites. Microfossils are rare, especially in the Hirnantian, but conodonts provide some useful markers just below and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…diamictite. This part of the δ 13 C org curve at Vinini Creek, Nevada (LaPorte et al 2009(LaPorte et al , Štorch et al 2011 and at several other sites (most notably at Mirny Creek, Siberia; Kaljo et al 2012) contains the base of the M. extraordinarius Zone. These data suggest that the M. ojsuensis Biozone of the uppermost Králův Dvůr Formation is most likely early Hirnantian in age.…”
Section: Stratigraphy and Correlationsmentioning
confidence: 99%
“…diamictite. This part of the δ 13 C org curve at Vinini Creek, Nevada (LaPorte et al 2009(LaPorte et al , Štorch et al 2011 and at several other sites (most notably at Mirny Creek, Siberia; Kaljo et al 2012) contains the base of the M. extraordinarius Zone. These data suggest that the M. ojsuensis Biozone of the uppermost Králův Dvůr Formation is most likely early Hirnantian in age.…”
Section: Stratigraphy and Correlationsmentioning
confidence: 99%
“…) and Mirny Creek (Koren & Sobolevskaya ; Kaljo et al . ). We have compared the levels of first occurrence of M. extraordinarius at these two sections with the GSSP horizon (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…At the time that the GSSP for the base of the Hirnantian was chosen, only one candidate section was formally considered, Wangjiawan North (Chen et al 2006), where the GSSP was chosen at the level marked by the FAD of Metabolograptus extraordinarius. For the purposes of our study, it can be compared with two other sections that are widely used as graptolitic reference sections for the base of the Hirnantian: Vinini Creek (LaPorte et al 2009;Storch et al 2011) (note that the graptolite range data in these more recent papers differ substantially from those in Finney et al 1999) and Mirny Creek (Koren & Sobolevskaya 2008;Kaljo et al 2012). We have compared the levels of first occurrence of Fig.…”
Section: Comparison Of Gssps With Other Candidate Sectionsmentioning
confidence: 99%
“…Even in Nevada the plateau of the HICE has been considered within the M. extraordinarius Biozone (see Kaljo et al 2008, p. 211). Melchin et al (2003) placed the peak of the HICE at the GSSP section in Dobs Linn, Scotland, within the M. persculptus Biozone, and in the Mirny Creek section in Russia the main peak is within the M. persculptus Biozone (Kaljo & Martma 2011;Kaljo et al 2012). Mitchell et al (2012) suggested that the HICE in the Nevada sections and Mirny Creek section showed marked double peaks, one in the M. extraordinarius Biozone and one in the M. persculptus Biozone.…”
Section: The Hicementioning
confidence: 97%